Wakaf Uang dalam Ekosistem Ekonomi Digital: Solusi Keuangan Islam untuk Era Industri 4.0 - Hasan, Zaenol; Musari, Khairunnisa; Makki, Mustaqim (Sharia Faculty Islamic Economic Law Study Department, 2025)
The advancement of the digital economy in the Fourth Industrial Revolution era has created new opportunities for optimizing Islamic financial instruments, including cash waqf. This study aims to conceptualize the digital transformation of cash waqf by exploring its fundraising mechanisms, product integration with Islamic fintech platforms, and governance models in the digital ecosystem. Employing a qualitative descriptive approach with library research methodology, this study utilizes a systematic literature review (SLR) to examine relevant academic sources and regulatory documents. The findings reveal that: (1) online fundraising through digital payment systems and Islamic crowdfunding platforms has significantly enhanced public participation and accessibility; (2) product innovation such as waqf-based insurance, corporate waqf, and share waqf has been facilitated through fintech integration, aligning with the objectives of maqasid al-shariah; and (3) digital governance models incorporating blockchain and good corporate governance (GCG) principles have improved transparency, accountability, and institutional credibility. This study contributes to Islamic economic literature by offering a theoretical framework that synthesizes classical waqf principles with modern financial technology. It also highlights the potential of digital cash waqf as a transformative tool for inclusive socio-economic empowerment, while noting the need for improved digital literacy, regulatory frameworks, and inter-sectoral collaboration.